2012
DOI: 10.1080/09603123.2011.605877
|View full text |Cite
|
Sign up to set email alerts
|

Urinary heavy metals and associated medical conditions in the US adult population

Abstract: Health effects of heavy metals have been widely investigated, but further evaluation is required to comprehensively delineate their toxicity. Using data from the 2007-2008 National Health and Nutrition Examination Survey, a multivariate logistic regression analysis was performed on 1,857 adults to examine the relationship between urinary heavy metals and various medical conditions. Cardiovascular diseases were correlated to cadmium (OR: 4.94, 95% CI: 1.48-16.56) and lead (OR: 5.32, 95% CI: 1.08-26.21). Asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 55 publications
5
80
0
Order By: Relevance
“…5 The 2007-2008 National Health and Nutrition Examination Survey of United States (NHANES) reported that the mean urinary Mo concentrations of both sexes in the general population range between 43.5 and 90.4 μg/g of creatinine in subjects aged 6 years and >20 years, respectively. 6 Mo toxicity has been evaluated mainly in animals and seems to be mediated by copper (Cu) concentration. 7 The main signs of Mo poisoning observed among animals are poor growth and anemia (rats, chickens, rabbits, cattle, and sheep), anorexia (rats), diarrhoea and achromotrichia (cattle and sheep), joint and bone deformities (rats, rabbits, cattle), central nervous system degeneration and loss of crimp in wool (sheep) and thyroidal injury, and hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…5 The 2007-2008 National Health and Nutrition Examination Survey of United States (NHANES) reported that the mean urinary Mo concentrations of both sexes in the general population range between 43.5 and 90.4 μg/g of creatinine in subjects aged 6 years and >20 years, respectively. 6 Mo toxicity has been evaluated mainly in animals and seems to be mediated by copper (Cu) concentration. 7 The main signs of Mo poisoning observed among animals are poor growth and anemia (rats, chickens, rabbits, cattle, and sheep), anorexia (rats), diarrhoea and achromotrichia (cattle and sheep), joint and bone deformities (rats, rabbits, cattle), central nervous system degeneration and loss of crimp in wool (sheep) and thyroidal injury, and hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Pollution of ground and surface waters with toxic metals ions leachate from industries and urban dumpsites is a major problem since most heavy metals like copper, cobalt, cadmium, chromium, lead, etc. are not biodegradable and hence they tend to accumulate in living organisms with an enduring toxic and carcinogenic effect on the body (Pfeiffer 1997;Desai and Kaler 2008;Araya et al 2005;Johnson et al 1992;Moradi et al 2012;Kim et al 2006;Mendy et al 2012). Water pollution and its remediation are principal health issues, and various procedures have been proposed including chemical precipitation, membrane filtration, ion exchange, coagulation, electrocoagulation, and adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Mo is considered an essential trace element. Due to the small sample size of this study, the scarce evidence about its potential toxicity in humans, 13,15,16,35,36 further research with a larger sample size and a detail evaluation of other potential dietary and environmental sources of Mo is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…However, in children from these women we observed a negative association between prenatal Mo exposure and infant psychomotor neurodevelopment. 16 Similarly, two studies have observed a possible association between Mo exposure with spermatic damage, 35 reproductive hormone alterations 36 and liver disorders 15 at BEs levels associated with toxicity in whole blood (0.45-22mg/L) or lower than those urinary BEs proposal levels for Mo.…”
Section: Discussionmentioning
confidence: 99%